Toward clean and fuel efficient automobiles : proceedings of an international conference, Berlin, 25-27 March 1991 = Vers la voiture propre à faible consommation : rapport d'une conférence internationale, Berlin, 25-27 mars 1991 (OECD documents, 1993)
"... papers presented at the international conference 'Tomorrow's Clean and Fuel-efficient Automobile: Opportunities for East-West Co-operation, held in Berlin on March 25-27, 1991." -- Foreword.